Economic growth and development in Macau (1999–2016): The role of the booming gaming industry. (May 2018) - Sheng, Mingjie; Gu, Chaolin
Abstract: In 2018, Macau will celebrate the 20th anniversary of its return to China. The past few years have witnessed brilliant economic achievements as well as a structural shift toward a gaming-industry dominated economy. Following so many years of rapid growth, it is essential to take stock of both the benefits and costs of gaming industry development. Accordingly, this paper analyzes the evolution of Macau's gaming industry between 1999 and 2016, and evaluates the industry's effects on local economic growth and urban development. As the paper shows, Macau has exhibited many of the symptoms typically associated with booming sectors in small economies, and has witnessed the similar effects widely experienced by western casino cities. However, Macau is also faced with some unique challenges, regarding its geographic location, size constraints, and political factors. These findings illustrate the difficulties that have accompanied Macau's economic achievements, but also call attention to opportunities in the next phase of Macau's development. Highlights: The period from 1999 to 2015 is marked by the opening-up of Macau's gaming market, the following-up explosive gaming growth, and the first period of decline in decades. The development of gaming industry has been shaped by actions of the local government as well as the Chinese central government. Macau displays many symptoms typically associated with booming sectors in small economies, such as high levels of investment and labor migration, growing economic vulnerability, and resource movement effects. Macau faces a set of unique challenges, including rapid expansion of non-tradeable sectors, foreign-dominated development, social divisions between local residents and imported workers, and worsening living conditions. It is advisable for Macau to enhance its tourism industry, to serve as a platform for promoting economic and trade relations between China and the Lusophone world, to help the expansion of local SMEs, and to look for more cooperation with mainland China.